Economic Perspectives on Setting up and Running Telepsychiatry Services in India. Issue 5 (October 2020) - Dewani, Khushboo; Basavarajappa, Chethan; Gowda, Guru S; Gowda, Mahesh; Srinivasa, Preeti; Muthyalappa, Chandrashekar; Kumar, Channaveerachari N; Manjunatha, Narayana; Vohra, Sandeep; Math, Suresh B
Background: Telemedicine Practice Guidelines, 2020 and Telepsychiatry Operational Guidelines, 2020 can be potential game changers in the practice of medicine in India. They provide legal grounds for the practice of telemedicine. The economics of setting up and running telepsychiatry services vis-à-vis in-person services in India is discussed in this paper to aid the practitioners in understanding the costs involved in each of these modalities. Methods: Costs for various hardware, software, real estate, and human resources are collated from various sources. Telepsychiatry vs. in-person setup is compared for the costs involved. Results: Telepsychiatry consultation will cost much lesser to that of in-person consultation. Conclusions: Telepsychiatry is an economically viable option. There are many benefits and hurdles in telepsychiatry practice. It is a step towards providing psychiatric services at the doorstep in compliance with the Mental Healthcare Act 2017, upholding the rights of persons with mental illness. It will benefit the practitioner, the patient, and the society.